Frustration and Creativity: Environmentalism in the Republic of Moldova - (:unkn) unknown (My University, 2013)
Through an ethnographic exploration of the diverse ways environmentalism has emerged in the Republic of Moldova, this dissertation seeks to provide insight into the changes occurring in Moldovan society. At first glance, Moldova's small yet diverse environmental community appears scattered and divided by age, Romanian or Russian language use, and urban or rural project location. While some environmentalists blame these divisions for the lack of a coherent movement, many also use these and other binaries in strategic ways to advance their projects. However, these categories cannot be so easily separated. Environmentalism, like many aspects of life in Moldova, is characterized by interconnections, overlaps, and ambiguity, stemming largely from the country's long history as a borderland. Though this ambiguity sometimes results in contradictions within projects, it can also result in a useful flexibility. Another thread that ties Moldovan environmental projects together is their embeddedness in the country's larger modernization strategy. Development programs are very visible in Moldova, a former Soviet state with a struggling economy and a weak government at the edges of both Europe and the former Soviet Union. Moldova's economic disadvantages and its historical ties to those across its borders contribute to an inclination to look abroad for solutions, and many environmentalists rely in part on international funding and environmental models to solve local problems. Moreover, a sense of how "the West" judges them contributes to a Moldovan tendency to see their country as "backward," and environmental projects often aim at "modernizing" the country in some way. The three case studies in this dissertation illustrate the themes of ambiguity, flexibility, and modernization through a focus on how environmentalists define and respond to various obstacles. The first case study looks at several rural projects using environmental funding to address sanitation problems in Moldovan villages. The second focuses on a protected areas project involving several well-established environmental NGOs in Chisinau. The third considers an attempt by urban, internationally-focused young people to create a new "eco" movement in Moldova.
Keywords: Environmentalism; Moldova; Post-Soviet